Destroying one Public Service Bargain Without Making Another: A Comment on Lowe and Pemberton, The Official History of the British Civil Service, Volume II: 1982–1997. Issue 1 (11th March 2021) - Diamond, Patrick
Abstract: This article responds to Lowe and Pemberton's second volume on the history of the civil service and analyses fundamental shifts in British governance at the centre that occurred during the 1980s and 1990s. The traditional 'public service bargain' (PSB) that underpinned the relationship between ministers and officials has been repeatedly undermined. The article examines how far prior civil service reforms relate to the changes of the contemporary era instigated by Conservative‐led governments since 2010. As Lowe and Pemberton's work illustrates, the impulse to reform the state and the managerial reforms it unleashed were long in the making. Their legacy can be traced to the emergence of Thatcherism after 1979. The core argument of the article is that the more recent efforts of the Johnson administration to transform the state and undermine the PBS were scarcely original. Rather, they consolidated and drew upon earlier initiatives.